Pembelajaran Matematika Berbasis CTL untuk Peserta Didik Berkebutuhan Khusus ADHD di Sekolah Dasar - Surmilasari, Nora; Marini, Arita; Maratun, Maratun; Prasrihamni, Mega (Universitas Negeri Makassar, 2022)
Attention deficit hyperactivity disorder (ADHD) is one of the diagnoses of children with special needs that are often found in elementary school students. They have difficulty in activities that require high concentration, including counting activities. This research is a narrative inquiry research that aims to describe the implementation of the Contextual Teaching Learning (CTL) method in mathematics learning applied by one of the teachers of SD Negeri 225 Palembang to students with ADHD. The data collection technique was done by interview. Research informants are teachers and parents of students diagnosed with ADHD. Based on the analysis of research data, it was concluded that the CTL model can be applied to mathematics learning for students diagnosed with ADHD by paying attention to several important things, namely determining the appropriate context for students, building closeness, making mature lesson plans, learning how to divert attention when instructed, patient and consistent.